On Topological Analysis of Niobium (II) Oxide Network via Curve Fitting and Entropy Measures - Muhammad Kamran Siddiqui; Sana Javed; Sadia Khalid; Mazhar Hussain; Muhammad Shahbaz; Samuel Asefa Fufa (Complexity)
The remarkable optical features of metallic nanoparticles have extensively developed the interest of scientists and researchers. The generated heat overwhelms cancer tissue incident to nanoparticles with no damage to sound tissues. Niobium nanoparticles have the ability of easy ligands connection so they are very suitable in treating cancer optothermally. A modern field of applied chemistry is chemical graph theory. With the use of combinatorial methods, such as vertex and edge partitions, we explore the connection between atoms and bonds. Topological indices play a vital part in equipping directions to treat cancers or tumors. These indices might be derived experimentally or computed numerically. Although experimental results are worthful but they are expensive as well, so computational analysis provides an economical and rapid way. A topological index is a numerical value that is only determined by the graph. In this paper, we will discuss the chemical graph of niobium (II) oxide. Additionally, each topological index is related with thermodynamical properties of niobium (II) oxide, including entropy and enthalpy. This has been done in MATLAB software, using rational built-in method.